Sparking Fire Under the Skin? Answers From the Association of Complement Genes With Pemphigus Foliaceus - Bumiller-Bini, Valéria; Cipolla, Gabriel Adelman; de Almeida, Rodrigo Coutinho; Petzl-Erler, Maria Luiza; Augusto, Danillo Gardenal; Boldt, Angelica Beate Winter (Frontiers in Immunology, 2018)
Skin blisters of pemphigus foliaceus (PF) present concomitant deposition of autoantibodies and components of the complement system (CS), whose gene polymorphisms are associated with susceptibility to different autoimmune diseases. To investigate these in PF, we evaluated 992 SNPs (single nucleotide polymorphisms) of 44 CS genes, genotyped through microarray hybridization in 229 PF patients and 194 controls. After excluding SNPs with minor allele frequency <1%, out of Hardy-Weinberg equilibrium in controls or in strong linkage disequilibrium (r²≥0.8), 201 SNPs remained for logistic regression. Polymorphisms of 11 genes were associated with PF. MASP1 encodes a crucial serine protease of the lectin pathway (rs13094773: OR=0.5, p=0.0316; rs850309: OR=0.23, p=0.03; rs3864098: OR=1.53, p=0.0383; rs698104: OR=1.52, p=0.0424; rs72549154: OR=0.55, p=0.0453). C9 (rs187875: OR=1.46, p=0.0189; rs700218: OR=0.12, p=0.0471) and C8A (rs11206934: OR=4.02, p=0.0323) encode proteins of the membrane attack complex (MAC) and C5AR1 (rs10404456: OR=1.43, p=0.0155), a potent anaphylatoxin-receptor. Two encode complement regulators: MAC-blocking CD59 (rs1047581: OR=0.62, p=0.0152) and alternative-pathway-blocking CFH (rs34388368: OR=2.57, p=0.0195). One encodes opsonin: C3 (rs4807895: OR=2.52, p=0.0239), whereas four encode receptors for C3 fragments: CR1 (haplotype with rs6656401: OR=1.37, p=0.0382), CR2 (rs2182911: OR=0.23, p=0.0263), ITGAM (CR3, rs12928810: OR=0.66, p=0.0435) and ITGAX (CR4, rs11574637: OR=0.63, p=0.0056). Associations reinforced former findings, regarding differential gene expression, serum levels, C3 and MAC deposition on lesions. Deregulation of previously barely noticed processes, e.g. the lectin and alternative pathways and opsonization-mediated phagocytosis, also modulate PF susceptibility. The results open new crucial avenues for understanding disease etiology and may improve PF treatment through additional therapeutic targets.